Keabsahan Akta Autentik Dari Risalah e-RUPS PT Terbuka Melalui Aplikasi eASY.KSEI - Krismanova Dwi Cahyasari (Officium Notarium, 2022)
The The implementation of e-GMS in public company (PT) can be carried out with an application called eASY.KSEI which according to the provisions requires that it be made in the form of an authentic deed. Hence this study discusses, first, whether the authentic deed originating from the minutes of the e-GMS of Public Company through the eASY.KSEI Application complies with the provisions of Law No. 40 of 2007 on Limited Liability Companies? second, how is the validity of the authentic deed made from the e-GMS of public company minutes through the eASY.KSEI Application. The type of research used is normative law with statutory and conceptual approaches. The results of this study conclude, first, the form of minutes of meetings made in the eASY.KSEI application is not in accordance with the Limited Liability Company Law, but the minutes have been specifically regulated in accordance with the provisions of the Republic of Indonesia Financial Services Authority Regulation No. 16/POJK.04/2020 on Implementation of Electronic General Meeting of Shareholders of Public Companies; and secondly, the validity of an authentic deed will be fulfilled if the formal and material requirements are fulfilled as stipulated in the provisions of the Notary Office Law.Key Word: Authentic Deed, Electronic General Meeting of Shareholders, eASY.KSEI Application AbstrakPelaksanaan e-RUPS PT Terbuka dapat dilakukan dengan sebuah aplikasi bernama eASY.KSEI yang dalam ketentuannya diwajibkan dibuat dalam bentuk akta autentik. Sehingga dalam penelitian ini dibahas mengenai, pertama, apakah akta autentik yang berasal dari risalah e-RUPS PT Terbuka melalui Aplikasi eASY.KSEI telah sesuai dengan ketentuan Undang-Undang No. 40 tahun 2007 tentang Perseroan Terbatas? kedua, bagaimana keabsahan akta autentik yang dibuat dari risalah e-RUPS PT melalui Aplikasi eASY.KSEI. Jenis penelitian yang digunakan adalah hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menyimpulkan, pertama, bentuk risalah rapat yang dibuat dalam aplikasi eASY.KSEI tidak sesuai dengan Undang-Undang Perseroan Terbatas namun risalah tersebut telah diatur secara khusus sesuai dengan ketentuan Peraturan Otoritas Jasa Keuangan Republik Indonesia No. 16/POJK.04/2020 tentang Pelaksanaan Rapat Umum Pemegang Saham Perusahaan Terbuka Secara Elektronik; dan kedua, keabsahan akta autentik akan terpenuhi apabila syarat formil dan materil terpenuhi sebagaimana diatur dalam ketentuan Undang-Undang Jabatan Notaris.Kata-kata Kunci: Akta Autentik, Rapat Umum Pemegang Saham Elektronik, Aplikasi eASY.KSEI